Disease Dynamics of the COVID-19 Outbreak and Detecting the Important Controlling Factors: A Model Based Study - Rana, Sourav; Das, Krishna pada; Das, Subhadipa; Ghosh, Shubhadeep (Discontinuity, Nonlinearity, and Complexity, 2026)
The worldwide rapid outbreak of coronavirus disease 2019 (COVID-19) has created a crisis in almost every country. The control of this disease possesses the ultimate challenge throughout the world. The mathematical model is an essential tool to study disease dynamics and is used to understand the impact of several control measures on disease propagation. In this work, we proposed and analyzed a compartmental model to study the spread of COVID-19 and its various control measures. The model parameters are influenced through different precautionary measures such as, social distancing, public awareness, improvement of hospital facilities, rapid case detection through testing, etc. These epidemiologically controllable parameters are directly linked with the disease spreading. Using partial rank correlation coefficient technique we observed that home isolations, self-awareness and social distancing measures have the most positive impact on the basic reproduction number (R_0). An effective control strategy of the disease spread can be implemented through these measures and in some special situations, the value of R_0 is less than 1 i.e. the disease can be controlled if the proper measures are implemented. Moreover, we observed that the recruitment rate plays a vital role in the long-term dynamics and due to the effect of recruitment, there may be a second peak or, the disease may co-exist in the population in absence of vaccination.